Effectiveness of preformed foot orthoses in reducing lower limb pain, swollen and tender joints and in improving quality of life and gait parameters in children with juvenile idiopathic arthritis: a randomised controlled trial (Protocol). Issue 1 (30th November 2017) - Fellas, Antoni; Singh-Grewal, Davinder; Chaitow, Jeffrey; Santos, Derek; Coda, Andrea
Abstract : Background: Many children and adolescents with juvenile idiopathic arthritis experience lower limb problems which may lead to physical disabilities significantly impacting on their quality of life and symptoms. Emerging evidence has identified the effective role of podiatry in the management of juvenile idiopathic arthritis, suggesting the clinical benefit of different orthotic therapies. Methods: This study will be a parallel-group designed, multicentre, randomised controlled trial, aiming to recruit 66 children and adolescents with juvenile idiopathic arthritis aged between 5 and 18 years. Those recruited will need to be diagnosed according to the International League of Associations for Rheumatology criteria, and present with lower limb joint pain, swelling and/or tenderness. Participants will be recruited from three outpatient hospital clinics in New South Wales, Australia. Participants will be randomly allocated to receive a trial or control intervention. The trial group will be prescribed a customised preformed foot orthoses; instead, the control group will receive a flat 1 mm insole with no corrective modifications. Primary outcome measure recorded will be pain. Secondary outcomes will be quality of life, foot disability, swollen and tender joint count and gait parameters (such as plantar pressures, walking speed, stance and swing time). The allocated foot orthoses will be worn for 12 months, with data collected at baseline, 4 weeks, 3, 6 and 12 months intervals. Group allocation will be concealed and all analyses will be carried out on an intention to treat. Discussion: The purpose of this trial is to explore the efficacy of a cost-effective, non-invasive podiatric intervention that will be prescribed at the initial biomechanical consultation. This approach will promote early clinical intervention, which is the gold standard in paediatric rheumatology. Furthermore, this study has the potential to provide new evidence for the effectiveness of a mechanical intervention alone to reduce swollen and tender joints in juvenile idiopathic arthritis. Trial registration number: This clinical trial has been registered with the Australian New Zealand Clinical Trials Registry: ACTRN12616001082493p. Ethics for this randomised controlled trial has been approved (16/09/21/4.03).